Providing an Anti-Marketing Model to Prevent Criminal Behaviors in Online and Digital Businesses - Ghasem Zarei; Younes Nikkhah (‫مدیریت بازرگانی)
Objective The development of the digital environment in most areas of business has led to an increase in deceptive practices and unconventional behaviors. With the advancement of the digital environment, unconventional channels have emerged, leading to various risks such as life, financial, and behavioral risks affecting individuals and businesses. Marketing operations face significant challenges without the presence of the digital environment, which serves as a crucial marketing platform. Certain profit-driven individuals exploit this expansive environment for fraudulent and unethical business practices. To curb criminal activities in the marketing sector, this study aims to introduce an anti-marketing model tailored for online and digital businesses and provide practical solutions. It seeks to address the gaps in the extant literature that have remained almost untouched by researchers.